Comparing the hemodynamic effect of a large arteriovenous fistula during high and low cardiac output states - Valerianova, A.; Mlcek, M.; Malik, J.; Grus, T.; Tejkl, L.; Kolosova, B.; Lejsek, V.; Kittnar, O. (Frontiers in Physiology, 2023)
Background: A large arteriovenous fistula (AVF) is a low-resistant circuit that affects organ perfusion and systemic hemodynamics even in standard conditions. The extent of its’ effect in critical states has not been elucidated yet. We used norepinephrine to create systemic vasoconstriction, dobutamine to create high cardiac output, and rapid right ventricle pacing as a model of acute heart failure in a porcine model of high-flow AVF circulation. Methods: The protocol was performed on nine domestic female pigs under general anesthesia. AVF was created by connecting two high-diameter ECMO cannulas inserted in the femoral artery and vein. Continuous hemodynamic monitoring was performed throughout the protocol. Three interventions were performed–moderate dose of norepinephrine (0.25 ug/kg/min), moderate dose of dobutamine (10 ug/kg/min) and rapid right ventricle pacing to simulate low cardiac output state with mean arterial pressure under 60 mmHg. Measurements were taken with opened and closed arteriovenous fistula. Results: Continuous infusion of norepinephrine with opened AVF significantly increased mean arterial pressure (+20%) and total cardiac output (CO) (+36%), but vascular resistance remained virtually unchanged. AVF flow (Qa) rise correlated with mean arterial pressure increase (+20%; R = 0.97, p = 0.0001). Effective cardiac output increased, leading to insignificant improvement in organ perfusion. Dobutamine substantially increased cardiac output with insignificant effect on AVF flow and mean arterial pressure. Carotid artery blood flow increased significantly after dobutamine infusion by approximately 30%, coronary flow velocity increased significantly only in closed AVF state. The effective cardiac output using the heart failure model leading to decrease of carotid artery flow and worsening of brain and peripheral tissue oximetry. AVF blood flow also dropped significantly and proportionally to pressure, but Qa/CO ratio did not change. Therefore, the effective cardiac output decreased. Conclusion: In abovementioned extreme hemodynamic conditions the AVF flow was always directly proportional to systemic perfusion pressure. The ratio of shunt flow to cardiac output depended on systemic vascular resistance. These experiments highlight the detrimental role of a large AVF in these critical conditions’ models.